Using the SF-36 measure to compare the health impact of multiple sclerosis and Parkinson's disease with normal population health profiles. Issue 6 (1st June 2003) - Riazi, A; Hobart, J C; Lamping, D L; Fitzpatrick, R; Freeman, J A; Jenkinson, C; Peto, V; Thompson, A J
Abstract : Objective: To examine the relative impact of two chronic neurological disorders, multiple sclerosis and Parkinson's disease, by comparing patients' scores on the medical outcomes study 36-item short form health survey (SF-36) with the health profile of the United Kingdom population norms. Methods: 638 people representing the full spectrum of multiple sclerosis and 227 patients with Parkinson's disease were studied. Health status was measured by the SF-36. Scores for the eight health domains were compared after controlling for age, sex, disease duration, mobility, social class, ethnicity, education, marital status, and employment status. Results: People with multiple sclerosis and those with Parkinson's disease had significantly worse health than the general population on all eight domains measured by the SF-36. The relative impact of multiple sclerosis and Parkinson's disease were similar, but multiple sclerosis resulted in poorer scores on physical functioning and better scores in mental health. People with mild multiple sclerosis who walked without an aid also had significantly worse scores in all dimensions than the general UK population. Conclusions: The results highlight the need for further research into aspects of health measured by the SF-36. Nevertheless, generic measures that are applicable across multiple diseases may fail to address clinically important aspects of the impact of specific disorders.